Investigating the roles of academic emotions in the relationship between agentic engagement and EFL achievement among Chinese undergraduate students - He, Hongwu (Frontiers in Psychology, 2025)
This study examines the relationships among agentic engagement, academic emotions, and English as a foreign language (EFL) achievement in Chinese undergraduate students, with a focus on variations across grade levels. Utilizing a quantitative design, data were collected from 221 English majors (111 first-year and 110 fourth-year undergraduate students) via questionnaires assessing agentic engagement and academic emotions, alongside English examination scores. Data analysis was conducted using SPSS Amos to explore moderating and mediating effects. Results reveal that none of the academic emotions showed significant moderating effects. Pride stands out because it fully mediated the impact of agentic engagement on English achievement across the entire sample (indirect effect = 0.246, p < 0.05), while hopelessness and anxiety demonstrated partial mediating effects. Grade-level differences were stark: for first-year undergraduate students, agentic engagement directly boosted EFL achievement, with emotions playing a negligible role. Conversely, among fourth-year undergraduate students, positive emotions fully mediated this relationship (indirect effect = 0.174, p < 0.05), with no significant direct effect. These findings highlight the stage-specific roles of academic emotions, with hopelessness amplifying engagement’s effect broadly and positive emotions like pride driving achievement in later years. Theoretically, this enriches models of engagement and emotion in EFL learning, emphasizing cultural and developmental nuances in China’s educational context. Practically, it suggests tailored strategies—promoting proactive engagement for novices and fostering positive emotions for advanced learners—to enhance EFL outcomes.